The Regional Western Sweden SOM Survey 2003 - SOM Institute, University of Gothenburg (University of Gothenburg, 2006)
Western SOM has been conducted yearly since 1992, but was initially limited to residents of Gothenburg and its surrounding municipalities. In 1998, the survey was extended to include the entire Västra Götaland County plus the municipality of Kungsbacka.

The purpose of the regional surveys is to enable SOM researchers to study attitudes and behaviour linked to local and regional issues. They emphasise public services and media, although many of the questions are identical with those used in National SOM in order to make the answers comparable both between the regions and with Sweden at large.

Purpose:

Study attitudes and behaviours that are linked to local and regional issues and phenomena

Detta är den tolfte studien i serien SOM-undersökningar genomförda i Västsverige. Undersökningen genomfördes med två olika enkätformulär: ett riktat till invånarna i Göteborg med kranskommuner och ett till dem hemmahörande i resterande delar av Västra Götaland. Enkätformulären innehåller till största delen gemensamma frågor. Några frågor är dock enbart ställda i en av de två enkäterna; framför allt handlar det om frågor enbart ställda i formuläret till invånarna i Göteborgsregionen. Båda enkäterna innehåller frågeområdena: Massmedier; Politik och samhälle; Samhälle och service; Trafik; Trygghet och säkerhet; Teknikinnehav och internet; Göteborgs-Posten; Aktiviteter och fritidsvanor; Göteborg; Arbetsliv; och Om dig själv.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 2003
Väst-SOM 2003
Keywords: internal politics; inrikespolitik; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap